2013
DOI: 10.1002/jcp.24329
|View full text |Cite
|
Sign up to set email alerts
|

RB1 in cancer: Different mechanisms of RB1 inactivation and alterations of pRb pathway in tumorigenesis

Abstract: Loss of RB1 gene is considered either a causal or an accelerating event in retinoblastoma. A variety of mechanisms inactivates RB1 gene, including intragenic mutations, loss of expression by methylation and chromosomal deletions, with effects which are species-and cell typespecific. RB1 deletion can even lead to aneuploidy thus greatly increasing cancer risk. The RB1gene is part of a larger gene family that includes RBL1 and RBL2, each of the three encoding structurally related proteins indicated as pRb, p107,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
127
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(136 citation statements)
references
References 125 publications
(144 reference statements)
1
127
0
3
Order By: Relevance
“…The retinoblastoma susceptibility gene (Rb) is a tumor suppressor gene mutated in a large variety of cancer (Di Fiore et al, 2013). Its tumor suppressive activity is at least partially dependent on its ability to induce cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…The retinoblastoma susceptibility gene (Rb) is a tumor suppressor gene mutated in a large variety of cancer (Di Fiore et al, 2013). Its tumor suppressive activity is at least partially dependent on its ability to induce cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…The growth suppressive function of the retinoblastoma protein (RB) is inhibited by direct inactivating mutations, or more commonly by changes in expression of its upstream regulators, including overexpression of cyclin D1, activating mutations in cyclin-dependent protein kinase 4 (CDK4), and inactivating mutations in p16 INK4A (inhibitor of cyclin-dependent kinase type 4, also called INK4A). 1 In addition, RB is inactivated by the viral oncoprotein E7, which promotes RB instability, and by E1A or SV40T, which disrupt the interaction between RB and the E2F family of DNA binding transcription factors (E2F). 1 We have shown that mouse double minute 2 homolog (MDM2) directly binds to the C-pocket of RB, leading to disruption of RB-E2F interaction and accelerated RB degradation.…”
mentioning
confidence: 99%
“…1 In addition, RB is inactivated by the viral oncoprotein E7, which promotes RB instability, and by E1A or SV40T, which disrupt the interaction between RB and the E2F family of DNA binding transcription factors (E2F). 1 We have shown that mouse double minute 2 homolog (MDM2) directly binds to the C-pocket of RB, leading to disruption of RB-E2F interaction and accelerated RB degradation. 2,3 In our recent study, we demonstrated that double minute X human homolog, (MDMX, also known as MDM4) can also bind to and promote RB degradation in an MDM2-dependent manner, thereby promoting tumor growth.…”
mentioning
confidence: 99%
“…Because the loss of RB1 causes subsequent hyperactivation (or deregulation) of E2F1, which should theoretically activate both cell-cycle progression and apoptosis, 19 we hypothesized that cancer cells constitutively expressing deregulated E2F1 must have an RB1-independent mechanism that does not allow E2F1 to induce apoptosis during serum starvation, but that instead leaves E2F1-induced cell-cycle progression intact.…”
mentioning
confidence: 99%